Analysis of primary side turn-to-turn short circuit fault in PT at the generator outlet and diagnosis using CSSA-GMM - Wei, Yang; Li, Chen; Ai, Yuangao; Shen, Hongwan; Zeng, Shai; Sun, Yue (Frontiers in Energy Research, 2024)
The potential transformer (PT) in power systems is responsible for converting high voltage into low voltage.However, an inter-turn short circuit fault on the primary side of the PT at the generator outlet can significantly reduce the phase voltage on the secondary side, leading to voltage imbalances and the generation of fundamental zerosequence voltage. This condition mimics a stator winding ground fault and often results in incorrect protection operation. To prevent such misoperations and develop new fault diagnosis methods, this paper first conducts an equivalent circuit analysis of PT inter-turn short circuits and employs numerical calculations to elucidate the causes of these misoperations. A fault simulation model is established using Simulink, which verifies the distinction between inter-turn short circuits and stator ground faults while studying their electrical characteristics. Based on this foundation, the paper proposes a fault diagnosis model utilizing a Gaussian Mixture Model (GMM) optimized by the Circular Sparrow Search Algorithm (CSSA), referred to as CSSA-GMM. By optimizing the GMM parameters with CSSA and performing a comprehensive analysis of voltage and current characteristics, the model effectively diagnoses inter-turn short circuit faults under varying shorted turn ratios, achieving a high recognition accuracy of 98%. This method clearly separates PT inter-turn short circuits from stator ground faults at the generator outlet. It offers new insights for identifying faults and supports the smart development of relay protection systems.